LIFE ACTIVITIES OF THE FAMILIES OF MILITARY SERVICEMEN IN THE CONDITIONS OF WAR AS A PSYCHOLOGICAL PROBLEM (Psychology Travelogs, 2024)
The article examines the life of servicemen's families in wartime conditions. It has been found that the war has a destructive effect on the livelihoods of the families of the combatants. This is due to the fact that the members of such families have many anxieties and worries about the life and health of their relatives, who defend the country with weapons in their hands. Added to this are problems with moving to new places of service, adaptation to new life circumstances, as well as the limited ability of a military serviceman, as a spouse, to fully fulfill family roles. Particular attention is paid to the families of military personnel who are experiencing non-normative family crises, which may include: serious illness (injury) of a family member, death (death) of a family member, divorce, adultery, remarriage. Unfortunately, these questions have not yet become the subject of a separate study by researchers. In the course of our research, it was found that the wives of combatants sometimes experience cognitive dissonance due to respect for their husband as a hero-defender and disrespect due to destructive behavior patterns (the roles of despot, demotivator, moralizer, etc.). Almost 100% of the women we interviewed, whose husbands take part in hostilities, indicated that they feel apprehensive about the future of their family and need psychological enlightenment and help with further planning of family life and restoration of harmonious relations with their partner. Uncertainty about the future and disappointment with the partner's behavior depletes women's internal resources and can lead to stress and psychosomatic problems. That is why it is necessary to provide high-quality psychological assistance both to a serviceman returning from a combat zone and to his family members.
Keywords: families of servicemen; daily life; conditions of war; psychological problem